Gadjah Mada International Journal Of Business: Examining the Effects of Presentation Patterns, Orders, and Information Types in Investment Decision Making - Luciana Spica Almilia, Jogiyanto Hartono, . Supriyadi, Ertambang Nahartyo (MM UGM, 2013)
This study aims to investigate the existence of Belief Model (BAM) developed by Hogarth and Einhorn (1992) in investment decision making. Particulary, this study examined: the effects of presentation patterns, presentation orders, and information types (accounting or non-accounting information) in investment decision making. This study used laboratory experiment to test the hypotheses. Hypotheses were tested using t-test. This study showed a â€œjudgement biasâ€ that is a recency which the effect of presentation pattern is consecutive is higher than unconsecutively.